2010
DOI: 10.12968/denu.2010.37.10.674
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Dentist in Sleep Disorders

Abstract: It is important that dentists are aware of the problem of sleep disorders and the potential they have to help in their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The results showed that dental professionals' experiences with OSA varied and that possible oral health conditions as a result of OSA, were not always recognized. These results are in agreement with other studies (Bian, 2004;Jauhar et al, 2010;Reibel et al, 2019), showing that lack of knowledge among dentists and dental hygienists about OSA and its treatment may result in difficulties detecting the condition and related oral health problems. A main theme from the participants in the present study was the need for more knowledge about OSA and a request for tools to identify patients with potential, untreated or treated OSA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results showed that dental professionals' experiences with OSA varied and that possible oral health conditions as a result of OSA, were not always recognized. These results are in agreement with other studies (Bian, 2004;Jauhar et al, 2010;Reibel et al, 2019), showing that lack of knowledge among dentists and dental hygienists about OSA and its treatment may result in difficulties detecting the condition and related oral health problems. A main theme from the participants in the present study was the need for more knowledge about OSA and a request for tools to identify patients with potential, untreated or treated OSA.…”
Section: Discussionsupporting
confidence: 93%
“…Reflecting on the overall result, it is important to increase the knowledge about the associations between oral health and OSA. OSA must be seen as an oral health determinant that needs to be recognized in the dental care appointment and a natural part in oral clinical examinations (Jauhar et al, 2010). Education about this relationship should also support interprofessional collaborations, promoting quality care for patients with potential, untreated or treated OSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First line treatment involves recommendations such as weight loss, smoking and alcohol cessation and modification of sleeping position from supine to side sleeping [10].…”
Section: Management Optionsmentioning
confidence: 99%